Effects of different amendments on aggregate stability and microbial communities of coastal saline–alkali soil in the Yellow River Delta. (18th January 2023) - Li, Shan; Yao, Yuanyuan; Yang, Mingchuan; Zhang, Yanpeng; Zhang, Shugang; Shen, Tianlin; Ding, Fangjun; Li, Ziyao; Liu, Wenzheng; Cui, Jiutao; Yang, Yuechao
Abstract: Organic amendments have been widely used in coastal saline–alkali soil remediation; however, the mechanisms involved and the interactions between organic and inorganic amendments are still unclear. In this work, furfural residue (particulate; C/N ratio: 51.87; O‐alkyl C + di‐O‐alkyl C: 42.35%, aromatic C: 40.89%) and black liquor (dissolved; C/N ratio: 3.11; O‐alkyl C + di‐O‐alkyl C: 32.20%, aromatic C: 28.32%) were tested to examine their effects on chemical properties, water‐stable aggregate fractions, chemical compositions of solid‐state soil organic matter (SOM), gloaming‐related soil protein contents, and microbial communities of coastal saline–alkali soil under a 400‐day incubation experiment. Furthermore, organic amendments mixed with mineral amendment (4:1) were employed to explore the interactions between organic and inorganic amendments. Furfural residue had stronger and longer effects on soil macroaggregate stability (~240 days, intense) than black liquor (~15 days, weak), and mineral amendment addition had a positive effect on the stability of microaggregates. Our results revealed that qualities (primary form, C/N ratio, and chemical composition) of organic amendment which can change microbial communities by increasing soil C/N ratio and effective chemical compositions of solid‐state SOM, are the key factors in promoting the rapid formation and longer stability of coastal saline–alkali soil aggregates. Moreover, inorganic amendment addition can further improve the formation and stability of microaggregates rather than those of macroaggregates. This study provided a much‐needed technical basis for remediation of coastal saline–alkali soil.